Research on Variable Universe Fuzzy PID Control Strategy of Pipe Lining Induction Heating System. (3rd December 2020) - Wang, Yuzhong; Wei, Min; Hu, Xue; Jiang, Minghong; Zhang, Lixin
Abstract : It is a promising heat supply strategy to use induction heating for the pipe lining process, but temperature control is hindering its application. In this study, we designed the variable universe fuzzy PID controller, and the lining induction heating system model was used to verify its performance. First, the transfer function parameters of the lining induction heating system are obtained by the step response method. Then, a point-by-point convergent interpolator is established through the contraction-expansion factors to realize the adaptive expansion of the fuzzy universe. Finally, the performance of PID, fuzzy PID, and variable universe fuzzy PID are compared through simulation experiments, and the ability of the controller to resist disturbance is verified by adding interference. The results show that the variable universe fuzzy PID controller can greatly improve the performance of fuzzy PID in response speed and settle time. The average stability error is smaller than PID and fuzzy PID control. It can meet the speed and accuracy requirements of the lining induction heating system. This research can be used as a reference for induction heating precise control and evidence that the variable universe fuzzy PID control can satisfy the lining induction heating process.